REPRESENTASI RESISTENSI PEREMPUAN DALAM FILM NGERI-NGERI SEDAP (2022) - Adinda, Sarah; Rahardjo, Turnomo; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
Dalihan Na Tolu as a Batak philosophy and cultural value is a principle in regulating social relations, customs, and providing clarity on the position of individuals in their groups. Even though Dalihan Na Tolu is not a social stratification, gender relations in Dalihan Na Tolu occur unequally. The role and position of men who strongly dominate, then causes women to be in an inferior position, both in everyday life and in the mass media or in the literary context, thus causing gender inequality. The existence of patriarchal cultural hegemony in the Batak ethnic group as well as the patrilineal kinship system that is adopted is a challenge for Batak women because of cultural norms that require women to always submit to men, the use of humor as an alternative narrative to challenge stereotypes. Resistance is then carried out by female characters. unusual and a challenge for Batak women because of cultural norms that require women to always submit to men, the use of humor as a way to fight back. The research objective is to determine the representation of women's resistance in the film Ngeri-Ngeri Sedap (2022), this research was studied using the Semiotics method by John Fiske, this research uses perspectives from Invitational Rhetoric Theory and Co-cultural Theory with a critical research paradigm. The conclusion of the research is that women's resistance can be carried out in stages, starting from small and hidden actions to bolder and more open actions. Women's resistance can also be carried out by involving strategies by utilizing a strong dominant cultural system, manipulating the situation, and also reaffirming the positive aspects of Dalihan Na Tolu cultural values on one of the Elek marboru stoves which is the power of women. Recommendations for further research are to explore discussions regarding stereotypes and cultural norms in other Batak sub-ethnic groups that are applied to certain genders, especially women, which ends in gender oppression and discrimination, then future researchers can also examine the issue of patriarchal culture in Indonesia from an ethnic perspective. -other ethnicities found in Indonesia and